CLIMATE RISK MANAGEMENT FOR SUSTAINABLE AGRICULTURE IN INDONESIA: A REVIEW / Pengelolaan Resiko Iklim untuk Pertanian Berkelanjutan di Indonesia: Sebuah Tinjauan - Elza Surmaini; Fahmuddin Agus (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
Climate-change related hazards, including drought, floods, extreme temperatures, and sea-water level rise have impacted Indonesia’s agriculture and these associated with economic losses. Therefore, it is increasingly important for farmers to be able to proactively anticipate the impact of weather and climate risks to protect their livelihoods through climate risk management (CRM) and to practice the sustainable agricultural production systems. Sustainable agriculture practices are needed to enhance resilience to adverse climate change events. This paper attempts to provide a review of agricultural risks related to climate change, principles and current CRM practices, and CRM practices at farm level based on agroecosystems, as well as approaches in enhancing agriculture CRM for sustainable agriculture development. The key technologies for lowland rice farming include alternate wetting and drying irrigation systems, and the use of drought, saline, and submergence tolerant rice varieties. For upland farming, water storage facilities such as water retardation pond, long storage, and channel reservoir are important. Subsequently, efficient water distribution systems such as drip irrigation, sprinkler irrigation, as well as capillary irrigation need enhancement. Various soil management technologies including minimum tillage and organic matter application are essential. For swampland one-way water management and conservation blocks, the “surjan” system, planting of adaptive varieties, and soil amelioration and fertilization are among the key treatments. Accurate climate forecasts may allow decision makers and farmers to make decisions to reduce negative impacts or take advantage of expected favorable climate. Finally, engagement of various actors, and capacity building is an integral part of CRM.Keywords: Climate, management, agriculture, sustainable, agroecosystem. AbstrakBencana iklim seperti kekeringan, banjir, suhu ekstrem dan kenaikan muka air laut berdampak negatif terhadap pertanian dan menimbulkan kerugian ekonomi. Oleh karena itu menjadi semakin penting bagi petani untuk proaktif mengantisipasi dampak risiko cuaca dan iklim untuk melindungi kehidupan mereka melalui pengelolaan risiko iklim dan menerapkan sistem produksi pertanian berkelanjutan. Praktik budi daya pertanian berkelanjutan memerlukan upaya peningkatan ketangguhan tanaman terhadap dampak kejadian iklim ekstrem. Tulisan ini merupakan tinjauan risiko pertanian terhadap perubahan iklim, prinsip dan praktik pengelolaan risiko iklim, dan praktik pengelolaan risiko iklim di tingkat petani berdasarkan agroekosistem, serta pendekatan untuk mendorong praktik pengelolaan risiko iklim untuk pertanian berkelanjutan. Teknologi utama untuk pertanian padi sawah termasuk pengairan berselang dan penggunaan varietas toleran kekeringan, salinitas, dan rendaman. Untuk pertanian lahan kering diperlukan bangunan pemanen air seperti embung, long storage, dan dam parit untuk pengairan tanaman. Selain itu, sistem distribusi air yang efisien seperti irigasi tetes, irigasi sprinkler, dan irigasi kapiler juga diperperlukan. Berbagai teknologi pengelolaan tanah termasuk pengolahan tanah minimum dan penggunaan bahan organik sangat penting. Pada lahan rawa pasang surut, pengelolaan air satu arah dan blok penyimpan air, sistem surjan, penanaman varietas adaptif, dan penggunaan amelioran dan pemupukan merupakan perlakuan utama. Prediksi iklim yang akurat dapat digunakan pengambil kebijakan dan petani dalam mengambil keputusan untuk mengurangi dampak negatif atau memanfaatkan kondisi iklim. Pelibatan berbagai aktor dan peningkatan kapasitas merupakan bagian integral dari pengelolaan risiko iklim.Kata kunci: Iklim, pengelolaan, pertanian, berkelanjutan, agroekosistem.